Fitting Tips and Visual Rehabilitation of Irregular Cornea with a New Design of Corneoscleral Contact Lens: Objective and Subjective Evaluation - Waleed Ali Abou Samra; Amani E. Badawi; Hanem Kishk; Ayman Abd El ghafar; Mohamed M. Elwan; Hossam Youssef Abouelkheir (Journal of Ophthalmology)
Objectives. To study the fitting and the visual rehabilitation obtained with a corneoscleral contact lens, namely, Rose K2 XL in patients with irregular cornea. Methods. This prospective study included 36 eyes of 36 patients with irregular cornea fitted with Rose K2 XL. Refractive and visual outcomes and mesopic and aberrometric parameters of fitted eyes were assessed at 2 weeks, 3 months, and 6 months after the initial lens use. Objective and subjective parameters of patient satisfaction and lens comfort were noted. Causes of lens discontinuation and complications were also recorded. Results. Average logMAR VA improved significantly from 0.95 ± 0.09 without correction to 0.04 ± 0.05 six months after lens wear. Similarly, mesopic and aberrometric measures were significantly improved. Statistical analysis of the subjective patients’ responses showed a significant acceptance of the lens by most of them. At the end of follow-up, the mean wearing time was 9.9 ± 2.9 hours per day. The most common cause of wearing discontinuation was persistent discomfort (16.7%) and high lens expenses(16.7%). Self-assessed questionnaire showed statistically significant improvement in nearly all measured subjective parameters. Conclusion. Rose K2 XL lenses provide patients with irregular cornea with both quantitative and qualitative optimal visual function with high degree of patient comfort and satisfaction.